Energy and exergy diagnostics of an industrial annular shaft limekiln working with producer gas as renewable biofuel - Camargos Tomás Pessoa Londe; da Costa Andréa Oliveira Souza; Costa Esly Ferreira Junior (Chemical Industry and Chemical Engineering Quarterly)
Quicklime, a globally significant commodity used in various industrial applications, is produced in limekilns requiring substantial energy, traditionally, from fossil fuels. However, due to escalating emission constraints and depletion of fossil fuel deposits, the quicklime industry explores alternative fuels, like biomass. The literature lacks feasibility diagnostic studies on limekilns using alternative biomass fuels. Thus, this article aims to conduct energy and exergy diagnostics on an industrial limekiln using producer gas derived from eucalyptus wood as a renewable biofuel. Employing industrial data and thermodynamics principles, the equipment was characterized, and results were compared with literature findings for similar limekilns using fossil fuels. The Specific Energy Consumption (𝑆𝐸𝑁) for the producer gas-operated limekiln was 4.8 GJ/tquicklime, with energy (𝜂𝑒𝑛) and exergy (𝜂𝑒𝑥) efficiencies of 54.6% and 42.2%. Overall energy (𝜂𝑒𝑛−𝑜𝑣𝑒𝑟𝑎𝑙𝑙) and exergy (𝜂𝑒𝑥−𝑜𝑣𝑒𝑟𝑎𝑙𝑙) efficiencies were 42.0% and 23.6%, respectively, lower than literature values. 𝑆𝐸𝑁𝑜𝑣𝑒𝑟𝑎𝑙𝑙was 7.6 GJ/tquicklime, higher than the literature results. Identified enhancements for both renewable and fossil fuel-powered limekilns involve recovering energy and exergy, including heat recovery from exhaust gases, minimizing thermal losses, and optimizing operational variables. These findings offer valuable insights for researchers exploring renewable biofuel adoption, like producer gas derived from eucalyptus wood, as alternatives to conventional fossil fuels in limekilns.